2008
DOI: 10.1002/jmv.21092
|View full text |Cite
|
Sign up to set email alerts
|

Infection and temporal arteritis: A PCR‐based study to detect pathogens in temporal artery biopsy specimens

Abstract: The possibility of infectious triggers stimulating the development of inflammatory vascular diseases has generated much recent interest. This study uses PCR to detect the presence of Chlamydia pneumoniae, parvovirus B19 and all the human herpes viruses except HHV8 in temporal artery biopsy specimens. Samples from 37 temporal artery biopsies with histological evidence of arteritis and 66 samples from histologically negative temporal artery biopsies, all from different patients, were negative for C. pneumoniae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 25 publications
0
23
1
1
Order By: Relevance
“…Analyses showed that all 90 patients were confirmed to have met the American College of Rheumatology classification criteria for TA [51]. The results of this study and study of Cooper et al [15] do not support a role for C. pneumoniae in the pathogenesis of TA.…”
Section: Giant Cell Arteritis Polymyalgia Rheumatica Temporal Artercontrasting
confidence: 58%
See 1 more Smart Citation
“…Analyses showed that all 90 patients were confirmed to have met the American College of Rheumatology classification criteria for TA [51]. The results of this study and study of Cooper et al [15] do not support a role for C. pneumoniae in the pathogenesis of TA.…”
Section: Giant Cell Arteritis Polymyalgia Rheumatica Temporal Artercontrasting
confidence: 58%
“…Although the majority of these studies initially focused on coronary heart disease [10,15,16]. More recent evidence also supports an association with stroke [14].…”
Section: Vascular Dementiamentioning
confidence: 99%
“…However, other larger studies have not corroborated this initial observation [135,136], with a similar frequency of PVB19 DNA localization found in arterial surgical specimens obtained from age-matched controls with atherosclerotic carotid/aortic disease [136]. An association of PVB19 with KD remains uncertain [137].…”
Section: Parvovirus B19mentioning
confidence: 66%
“…Several studies using polymerase chain reaction to detect the presence of Chlamydia pneumoniae, parvovirus B19, and several of the human herpes viruses in TAB specimens have yielded negative results. 26,27 Some still hypothesize the existence of a triggering antigen of unknown nature activating T-cells in the artery wall, following an immune response to infection. 28 Evidence in favor of this is a dual peak in cases of PMR and GCA in association with seasonal variation in Danish respiratory infections (specifically Mycoplasma pneumoniae, Parvovirus B19, and Chlamydia pneumoniae).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%